A Reliable Method to Quantify Sildenafil and its Metabolite N-Demethylsildenafil by HPLC in Plasma of Children - Ramírez-Mendiola, B.; Flores-Pérez, C.; García-Álvarez, R.; Juárez-Olguín, H.; Flores-Pérez, J.; Chávez Pacheco, J. L. (Drug Research, 2013)
The aim of this study was to develop a simple method for quantifying plasma levels of sildenafil and its metabolite by liquid chromatography with a C18 reverse-phase column and UV detection. For both compounds, linearity was assessed in the range from 10 and 1 000 ng · ml−1 and had correlation coefficients of r=0.995 and r=0.997 for sildenafil and its metabolite, respectively. The inter- and intra-day coefficients of variation was<5.3%. The limits of detection and quantification were 1 and 10 ng · ml−1. Drug levels were determined satisfactorily in two patients. A simple and reliable method was developed for use in children with Pulmonary Arterial Hypertension under treatment with sildenafil.
Keywords: children; liquid chromatography; sildenafil; pharmacokinetics; plasma levels